RESPON PUPUK DAUN NPK TERHADAP PERTUMBUHAN Nepenthes ventrata DAN Nepenthes neglecta - Muhammad Mansur; Saefudin .; Fauzia Syarif (Jurnal Teknologi Lingkungan, 2010)
Leaf NPK fertilizer experiments on pitcher plant (Nepenthes neglecta and ventrata) conducted in May 2008 to March 2009 in a greenhouse, Botany Division, Research Center for Biology-LIPI, Cibinong Science Center, Cibinong. The objective is to study the effect of leaves NPK fertilizer on the growth of the two Nepenthes species tested. Experiments using Random Complete Factorial Design with two factors, namely the two Nepenthes species and threedoses of fertilizer each treatment repeated six times. Growth parameters measured include; long shoot leaves, plant height, number of leaves, number of mature pitchers and growth pitchers. Results showed that the dose of NPK fertilizer provided (2 and 4 ml / lt) have no effect on plant height and number of leaves, but little effect on the number of mature pitchers thanthe control plants. The statistical tests also showed no interaction between the two Nepenthes species with a given dose of fertilizer on the growth of plants. Minimum-maximum temperature recorded in the greenhouse during the experiment was 22.20C and 38.50C. Meanwhile, air humidity between 43,6-64,7%.Key words: Leaf NPK fertilizer, plant growth, pitcher plant